Penegakan Hukum terhadap Tindak Pidana Korupsi menurut Sistem Peradilan Pidana Indonesia - Sukmareni, Sukmareni (Pagaruyuang Law Journal, 2018)
The success or failure of corruption law enforcement in Indonesia depends on the work of any component of the criminal justice system (SPP) itself, ranging from investigation, prosecution, court examination and criminal prosecution.The formulation of the issues raised in this study (1) Is the pattern of law enforcement that has been regulated in the Indonesian criminal justice system has been able to eradicate corruption in Indonesia to date? (2) What is the ideal pattern of law enforcement against corruption under the Indonesian criminal justice system? This researarch is descriptive research using normative juridical approach, by using legal materials as secondary data. Which legal substance consists of primary, secondary and tertiary legal materials, related to law enforcement against corruption in Indonesia's criminal justice system, analyzed using qualitative analysis. The Pattern enforcement in the SPPI still has not been able to enforce the maximal law enforcement against the TPK perpetrators, because there are still some weaknesses and problems, there is still overlapping of corruption arrangements, the quality of the judiciary has not been able to create justice in the community, the supervisory system on the performance of law enforcement officials with the law enforcement of corruption because it is not yet integrated and not yet clearly regulated, once the sanction given is still not maximized so it has not caused a deterrent effect to the perpetrator The ideal pattern of law enforcement against the TPK perpetrators required changes, improvements and improvements in various aspects above, such as regulatory reform, independence to four sub SPPI, improving the judicial supervision system as well as giving maximum sanction and more severe to the perpetrators so that cause the effects of good for the perpetrators and against other communities.